Health Impact and Cost-Effectiveness of Achieving the National Salt and Sugar Reduction Initiative Voluntary Sugar Reduction Targets in the United States: A Microsimulation Study. Issue 17 (26th October 2021) - Shangguan, Siyi; Mozaffarian, Dariush; Sy, Stephen; Lee, Yujin; Liu, Junxiu; Wilde, Parke E.; Sharkey, Andrea L.; Dowling, Erin A.; Marklund, Matti; Abrahams-Gessel, Shafika; Gaziano, Thomas A.; Micha, Renata
Abstract : Background: High intake of added sugar is linked to weight gain and cardiometabolic risk. In 2018, the US National Salt and Sugar Reduction Initiative proposed government-supported voluntary national sugar reduction targets. This intervention's potential effects and cost-effectiveness are unclear. Methods: A validated microsimulation model, CVD-PREDICT (Cardiovascular Disease Policy Model for Risk, Events, Detection, Interventions, Costs, and Trends), coded in C++, was used to estimate incremental changes in type 2 diabetes, cardiovascular disease (CVD), quality-adjusted life-years (QALYs), costs, and cost-effectiveness of the US National Salt and Sugar Reduction Initiative policy. The model was run at the individual level, incorporating the annual probability of each person's transition between health statuses on the basis of risk factors. The model incorporated national demographic and dietary data from the National Health and Nutrition Examination Survey across 3 cycles (2011 through 2016), added sugar-related diseases from meta-analyses, and policy costs and health-related costs from established sources. A simulated nationally representative US population was created and followed until age 100 years or death, with 2019 as the year of intervention start. Findings were evaluated over 10 years and a lifetime from health care and societal perspectives. Uncertainty was evaluated in a 1-way analysis by assuming 50% industry compliance and probabilistic sensitivity analyses through a second-order Monte Carlo approach. Model outputs included averted diabetes cases, CVD events and CVD deaths, QALYs gained, and formal health care cost savings, stratified by age, race, income, and education. Results: Achieving the US National Salt and Sugar Reduction Initiative sugar reduction targets could prevent 2.48 million CVD events, 0.49 million CVD deaths, and 0.75 million diabetes cases; gain 6.67 million QALYs; and save 160.88 billion net costs from a societal perspective over a lifetime. The policy became cost-effective (<150 000/QALYs) at 6 years, highly cost-effective (<50 000/QALYs) at 7 years, and cost-saving at 9 years. Results were robust from a health care perspective, with lower (50%) industry compliance, and in probabilistic sensitivity analyses. The policy could also reduce disparities, with greatest estimated health gains per million adults among Black or Hispanic individuals, lower income, and less educated Americans. Conclusions: Implementing and achieving the US National Salt and Sugar Reduction Initiative sugar reformation targets could generate substantial health gains, equity gains, and cost savings. Abstract : Supplemental Digital Content is available in the text.